Challenges for the implementation of World Health Organization guidelines for acute stress, PTSD, and bereavement: a qualitative study in Uganda. (December 2015) - Kane, Jeremy; Adaku, Alex; Nakku, Juliet; Odokonyero, Raymond; Okello, James; Musisi, Seggane; Augustinavicius, Jura; Greene, M.; Alderman, Steve; Tol, Wietse
Abstract Background In 2013, the World Health Organization (WHO) published new guidelines for the management of conditions specifically related to stress, including symptoms of acute stress, bereavement, and post-traumatic stress disorder (PTSD). It is important to evaluate potential challenges for the implementation of these guidelines in low-resource settings, however, there is a dearth of research in this area. The current qualitative study aimed to assess perspectives on the feasibility and acceptability of the new guidelines in four clinics that provide mental health services in post-conflict northern Uganda. Methods In-depth interviews were conducted with 19 mental health-care providers and program developers in northern Uganda to address three major research objectives: (1) describe the current standard practices and guidelines used for treating conditions related to stress in Uganda; (2) identify barriers and challenges associated with implementing the new WHO guidelines; and (3) identify and describe potential strategies for overcoming these barriers and challenges. An emergent thematic analysis was used to develop a coding scheme for the transcribed interviews. Results Practices for managing conditions related to stress included group psychological interventions, psychoeducation, and medication for clients with severe signs and symptoms. Several themes were identified from the interviews on barriers to guideline implementation. These included (1) a lack of trained and qualified mental health professionals to deliver WHO-recommended psychological interventions; (2) a perception that psychological interventions developed in high-income countries would not be culturally adaptable in Uganda; and (3) reluctance about blanket statements regarding medication for the management of acute stress symptoms and PTSD. Identified strategies for overcoming these barriers included (1) training and capacity building for current mental health staff; (2) a stepped care approach to mental health services; and (3) cultural modification of psychological interventions to improve treatment acceptability by clients. Conclusions Guidelines were viewed positively by mental health professionals in Uganda, but barriers to implementation were expressed. Recommendations for implementation include (1) strengthening knowledge on effectiveness of existing cultural practices for improving mental health; (2) improving supervision capacity of current mental health staff to address shortage in human resources; and (3) increasing awareness of help-seeking clients on the potential effectiveness of psychological vs. pharmacological interventions.